Багатофункціональний блок подразнення зворотного гортанного нерва у задачі його ідентифікації - Дивак, Микола Петрович; Тимець, Володимир Іванович; Дивак, Андрій Миколайович (Vinnytsia National Technical University, 2020)
The task of creation and research of recurrent laryngeal nerve identification system with multifunctional block of surgical wound tissues stimulation has been considered in the paper. Object of the study is the process of recurrent laryngeal nerve monitoring during neck surgery. A complex system for recurrent laryngeal nerve identification among the surgical wound tissues during the neck surgery has been proposed. The experimental researches of application of electrophysiological method of surgical wound tissues stimulation with different characteristics of electric current formed by the multifunctional block, have shown the highest effectiveness in the case of use of the alternating current with the frequency of 300 Hz. The recurrent laryngeal nerve identification system with the multifunctional block of surgical wound tissues stimulation has been created and approbated during the thyroid gland surgeries. Also, the necessity of further studies of the proposed method and system for the case of use of pulse current with bipolar impulses has been established.